Marketing Strategy of MSME Products as an Effort to Improve the Economy of Local Communities in Belawa Tourism Village, Cirebon Regency - Dian Fitriyana; Ratna Puspita Dewi (Ann Publisher, 2026)
Background. Effective and innovative marketing strategies can be a key factor in increasing income and fostering economic growth in the Tourism Village. MSMEs are an important sector in supporting the development of tourist villages because they serve as drivers of the community's economy by leveraging local potential. Therefore, the right marketing strategy is needed. Aims. The urgency of the research arises from the obstacles faced, including limited human resources, insufficient training, limited innovation in marketing, and low use of digital media for promoting MSME products. Method. This study uses a descriptive qualitative method, including interviews, observations, documentation, and literature reviews. The study's results show that MSMEs' marketing strategy in Belawa Tourism Village remains conventional and has not been integrated with digital strategies. Conclusion. MSME actors rely more on direct sales to tourists and word-of-mouth promotions. However, there is significant potential for growth through social media-based marketing strategies, product quality improvements, and strengthened local branding. Implementation. Village government support and training for MSME actors are urgently needed to improve product competence and competitiveness.